The Effect of Internet Addiction on Sleep Quality in Padang State University Students - Al Ardhi, Ferhan; Rinaldi (Causalita, 2026)
Student focus and attention on course material during lectures are fundamental elements for achieving academic success. However, sleepiness in the classroom often serves as a primary obstacle, hindering students from absorbing information optimally. A key physiological factor underlying this issue is poor sleep quality among students. In the current digital era, such sleep pattern disturbances are frequently triggered by excessive and uncontrolled internet use, leading to tendencies of addiction. This study aims to empirically examine the influence of internet addiction on sleep quality among students at Universitas Negeri Padang. This research employs a quantitative approach with a correlational design. The sample consisted of 256 active students selected using a purposive sampling technique. Data collection was conducted using two validated instruments: the Internet Addiction Test (IAT) to measure the level of internet dependency and the Pittsburgh Sleep Quality Index (PSQI) to evaluate the subjects' sleep quality over the past month. Data analysis was performed using the Spearman Rank correlation test. The results revealed a correlation coefficient of 0.562 with a valid significance level. This figure indicates a moderately strong and positive relationship between the two variables; meaning that higher levels of internet addiction correspond to poorer sleep quality among students. These findings suggest the need for interventions regarding digital media usage management to improve student sleep hygiene, which is ultimately expected to enhance focus and academic performance.